Double-Blind, Placebo-Controlled Pilot Randomized Trial of Methylprednisolone Infusion in Pediatric Acute Respiratory Distress Syndrome. Issue 3 (March 2015) - Drago, Bonny B.; Kimura, Dai; Rovnaghi, Cynthia R.; Schwingshackl, Andreas; Rayburn, Mark; Meduri, G. Umberto; Anand, Kanwaljeet J. S.
Abstract : Objective: Low-dose methylprednisolone therapy in adults with early acute respiratory distress syndrome reduces systemic inflammation, duration of mechanical ventilation, and ICU length of stay. We report a pilot randomized trial of glucocorticoid treatment in early pediatric acute respiratory distress syndrome. Design: Double-blind, placebo-controlled randomized clinical trial. Setting: Le Bonheur Children's Hospital, Memphis, TN. Patients: Children (0–18 yr) with acute respiratory distress syndrome undergoing mechanical ventilation. Interventions: Patients were randomly assigned to steroid or placebo groups within 72 hours of intubation. IV methylprednisolone administered as loading dose (2 mg/kg) and continuous infusions (1 mg/kg/d) on days 1–7 and then tapered over days 8–14. Both groups were ventilated according to the Acute Respiratory Distress Syndrome Network protocol modified for children. Daily surveillance was performed for adverse effects. Measurements and Main Results: Thirty-five patients were randomized to the steroid ( n = 17, no death) and placebo groups ( n = 18, two deaths). No differences occurred in length of mechanical ventilation, ICU stay, hospital stay, or mortality between the two groups. At baseline, higher plateau pressures ( p = 0.006) and lower Pediatric Logistic Organ Dysfunction scores ( p = 0.04) occurred in the steroid group; other characteristics were similar. Despite higher plateau pressures on days 1 ( p = 0.006) and 2 ( p = 0.025) due to poorer lung compliance in the steroid group, they had lower PaCO2 values on days 2 ( p = 0.009) and 3 ( p = 0.014), higher pH values on day 2 ( p = 0.018), and higher PaO2 /FIO2 ratios on days 8 ( p = 0.047) and 9 ( p = 0.002) compared with the placebo group. Fewer patients in the steroid group required treatment for postextubation stridor ( p = 0.04) or supplemental oxygen at ICU transfer ( p = 0.012). Steroid therapy was not associated with detectable adverse effects. Conclusion: This study demonstrates the feasibility of administering low-dose glucocorticoid therapy and measuring clinically relevant outcomes in pediatric acute respiratory distress syndrome. Changes in oxygenation and/or ventilation are consistent with early acute respiratory distress syndrome pathophysiology and results of similar clinical trials in adults. We propose and design a larger randomized trial to define the role of glucocorticoid therapy in pediatric acute respiratory distress syndrome.